Quality Assessment of Mature Unripe Pawpaw (Carica papaya) Fruit Powder as a Stabilizer in Thermized Yoghurt - Tersoo-Abiem, Evelyn Mnguchivir; Abel, Christopher Omale; Akpensuen, Mfe Samuel (European Journal of Applied Sciences, 2024)
Pawpaw fruit powders were produced from two mature unripe Carica papaya fruit cultivars via sun-drying and oven drying respectively, and were used to stabilize thermized yoghurt, at 0, 1, 2 and 3% concentrations respectively. The pawpaw fruit powders were evaluated for functional, physicochemical and microbial quality. The values for pH, TTA, TSS and moisture content ranged from 5.51±0.01 to 5.71±0.01, 0.11±0.01 to 0.13±0.01, 2.41±0.01 to 2.91±0.01 and 13.35 ±0.21 to 14.90±0.14 respectively. The functional properties of the fruit powders revealed bulk density, water absorption capacity, oil absorption capacity, emulsion capacity and foam capacity values ranged from 0.46±0.01 to 0.76±0.01, 0.81±0.01 to 1.61±0.01, 0.81±0.01 to 2.60±0.01, 4.70±0.07 to 7.95±0.07 and 39.21±0.01 to 48.05±0.07 respectively, while the microbial load of the powders were within acceptable levels. Results of the physicochemical analyses of thermized yoghurt with addition of pawpaw powder at different concentrations for pH, total soluble solids, specific gravity and TTA values ranged from 5.39±0.01 to 5.67±0.02, 11.72±0.03 to 12.61±0.01, 1.00±0.00 to 1.19±0.00 and 0.01±0.00 to 0.21±0.01. The microbial load of the stabilized thermized yoghurt showed no significant bacterial and fungal count. Results of sensory analyses revealed that 1% pawpaw fruit powder addition to thermized yoghurt was the most preferred.